1999
DOI: 10.1021/jp993318q
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Isolation and Density Functional Study of the Reaction of OVCl3 with CH3OH:  Synthesis and Characterization of Cl2V(O)OCH3

Abstract: The matrix isolation technique has been employed to investigate the reaction of OVCl3 with CH3OH. Using twin jet deposition, the initial intermediate in the mechanism was identified as a weakly bound molecular complex. This species is characterized by perturbations to the C−O, VO, and V−Cl stretching modes. Merged jet deposition, with a room-temperature reaction zone, led to complete conversion to Cl2V(O)OCH3, the second intermediate in the reaction sequence, through HCl elimination from the initial complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…Past studies in this laboratory have examined the matrixisolated products of the thermal and photochemical reactions of CrCl 2 O 2 , OVCl 3 , and OVF 3 with organic and inorganic substrates [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Specifically, two recent studies in this lab [33,34] examined the reactions of CrCl 2 O 2 with benzene and with methyl-substituted benzenes.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies in this laboratory have examined the matrixisolated products of the thermal and photochemical reactions of CrCl 2 O 2 , OVCl 3 , and OVF 3 with organic and inorganic substrates [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Specifically, two recent studies in this lab [33,34] examined the reactions of CrCl 2 O 2 with benzene and with methyl-substituted benzenes.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This laboratory has studied the reaction of these transition-metal compounds and several related species with small organic and inorganic substrates containing a heteroatom. [8][9][10][11][12][13] These studies have permitted the identification of a sequence of intermediates in each system from which a reaction mechanism was (at least partially) deduced. Wistuba and Limberg have focused on the reaction of CrCl 2 O 2 with alkenes and alkynes 14,15 and have reported several novel intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been applied to the study of a wide range of species, including radicals, weakly bound molecular complexes, and molecular ions. Recent studies from this laboratory have focused on the sequence of intermediates formed in the reactions of OVCl 3 and CrCl 2 O 2 with small organic substrates, as well as with NH 3 . , These studies have demonstrated that these reactions occur through the formation of an initial 1:1 complex, followed by thermal and/or photochemical elimination of HCl. In addition, since impurity levels of water are always present in matrix isolation studies, a knowledge of the spectrum of possible reaction products of OVCl 3 and CrCl 2 O 2 with H 2 O is important.…”
Section: Introductionmentioning
confidence: 99%